2018
DOI: 10.1364/oe.26.013543
|View full text |Cite|
|
Sign up to set email alerts
|

Scanning two-photon continuous flow lithography for synthesis of high-resolution 3D microparticles

Abstract: Demand continues to rise for custom-fabricated and engineered colloidal microparticles across a breadth of application areas. This paper demonstrates an improvement in the fabrication rate of high-resolution 3D colloidal particles by using two-photon scanning lithography within a microfluidic channel. To accomplish this, we present (1) an experimental setup that supports fast, 3D scanning by synchronizing a galvanometer, piezoelectric stage, and an acousto-optic switch, and (2) a new technique for modifying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Eventually, the uFlow and FlowSculpt may merge into a single software, but their current architectures have different intent from the ground-up: uFlow for visualization (with little regard for efficiency), and FlowSculpt for optimization (which would be encumbered by uFlow's processes), making integration complex and a low-priority goal. Beyond these developments in the software, FlowSculpt itself can be brought into other regimes of hierarchical design, such as tailored 3D particles via stop-flow lithography, 4,6 transient liquid molding, 5 or continuous-flow lithography, 14 enabling a new class of complex microfluidic engineering. We also anticipate that FlowSculpt will find more general use in engineering flow streams as more disciplines become aware of its capability, especially in manipulating material concentrations or distributions in microfluidic flow applications.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, the uFlow and FlowSculpt may merge into a single software, but their current architectures have different intent from the ground-up: uFlow for visualization (with little regard for efficiency), and FlowSculpt for optimization (which would be encumbered by uFlow's processes), making integration complex and a low-priority goal. Beyond these developments in the software, FlowSculpt itself can be brought into other regimes of hierarchical design, such as tailored 3D particles via stop-flow lithography, 4,6 transient liquid molding, 5 or continuous-flow lithography, 14 enabling a new class of complex microfluidic engineering. We also anticipate that FlowSculpt will find more general use in engineering flow streams as more disciplines become aware of its capability, especially in manipulating material concentrations or distributions in microfluidic flow applications.…”
Section: Resultsmentioning
confidence: 99%
“…Many current applications of flow sculpting were devised and implemented by inertial microfluidics experts, and even then, they sculpted relatively simple flow shapes that were achieved through trial-and-error design. A clear example of this difficulty is particle fabrication via flow sculpting, which remains competitive with state-of-the-art methods such as PRINT, 12 SEAL, 13 two-photon lithography, 14 and hollow fiber templating 15 due to the ability to create multi-material shaped 3D particles at high-throughput using basic microfluidic tools such as soft lithography 16 and 3D printing. 6 However, the flow sculpting approaches currently require the target 3D particle shape to comprise of the intersection of two orthogonally extruded 2D shapes: one from the shape of the sculpted flow stream (which contains a polymer precursor with a photoinitiator), and the other from an optical mask (which shapes polymerizing ultraviolet light).…”
Section: Introductionmentioning
confidence: 99%
“…[16,17] In addition, spherical particles have more limited barcoding options, and it has been reported that the presence of surfactants leads to higher rates of transport of products of reactions through the continuous oil phase, reducing sensitivity of enzymatic assays. [18,19] A range of fabrication methodologies have been explored over the past decade to create particles with different shapes and functionalities using continuous [20][21][22][23][24] or stop flow lithography techniques [25][26][27][28] combined with hydrodynamic focusing, [29][30][31][32] magnetically tunable color printing, [12,33] vertical flows, [34] structured hollow fibers [35] or inertial forces. [36][37][38][39] Particles comprised of layers of hydrophobic and hydrophilic materials were shown to selectively interact and assemble around aqueous drops.…”
Section: Introductionmentioning
confidence: 99%
“…Singh, Koch & Stroock (2013) identified ring-shaped particles which do not tumble in shear flow, in contrast to the tumbling behaviour of axisymmetric particles reported by numerous earlier works; the particle shapes were derived as perturbations to a circular shape to obtain zero torques on the particle. Uspal & Doyle (2014) designed self-aligning and centreline-focusing characteristics of asymmetric particles in Hele- Shaw flowspecifically, 'dumbbell' and 'trumbbell' shapes. Further motivating study of the inverse problem in fluid particle systems is the rapidly developing capabilities of particle fabrication techniques (Paulsen 2017;Shaw et al 2018;Yuan et al 2018;Wu et al 2018). These approaches enable scalable fabrication of arbitrary-shaped microparticles, presenting an abundant landscape for the design of customized microparticles for applications in biosensing and self-assembly.…”
Section: Introductionmentioning
confidence: 99%